Implementation of Early Warning Score (EWS) in Inpatient Ward: Scooping Review - Suprayogi, Suprayogi; Noviani Hemu, Viky; Setiyarini, Sri (International Journal of Health Science and Technology, 2023)
Early Warning Score (EWS) Implementation in Inpatient Ward: Scooping Review.The implementation of EWS is known to reduce the worsening rate of patients in the inpatient ward, accuracy in implementing can affect decision making in treating patients. Research shows that there is still little literature review that discusses the application of EWS. Therefore, it is necessary to conduct a scooping review related to the application of EWS. The purpose of this study was to identify how to apply EWS in inpatient wards in hospitals. The research method follows the framework of Arksey and O'Malley. The scooping review was conducted by 3 databases of PubMed, ScienceDirect, Scopus published from 2014-2023 in March, using English and Indonesian which discussed the implementation of EWS in hospitals using  the keywords  'Nurse', 'Early Warning Score', 'Early Warning System', detect deterioration patient'. The results obtained  as many as 179 potentially relevant articles, 7 articles identified. The findings revealed that the application of EWS carried out in the hospital consisted of recording observation sheets, frequency of patient monitoring according to the EWS score, actions according to the EWS protocol applied and the time of measurement of patient vital signs